Electrode for lithium secondary battery, method for manufacturing same, and lithium secondary battery
By forming overlapping electrode active material layers and insulating layers on the electrodes of the lithium secondary battery and controlling the thickness ratio, the short circuit problems caused by insufficient heat resistance of the lithium secondary battery separator and irregular electrode edges are solved, and the battery is improved The insulation and cohesive strength enhance the stability and performance of the battery.
Patent Information
- Application Number
- CN202411423277.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-01
- Filing Date
- 2019-02-01
- Publication Date
- 2024-12-20
AI Technical Summary
The separator heat resistance of existing lithium secondary batteries is insufficient, resulting in thermal runaway during internal short circuits, and irregular electrode edges lead to a high possibility of short circuits, affecting battery performance.
The electrode active material layer and the insulating layer are formed on the electrode current collector and overlap in some areas. The ratio of the insulating layer thickness to the electrode active material layer thickness is between 0.02 and 0.4, and the wet coating method is used to simultaneously dry it The electrode active material layer and insulating layer enhance cohesive strength and insulating properties.
It significantly improves the insulation and cohesive strength between battery components, prevents corrosion in overlapping areas, enhances the quality and stability of the battery, reduces the risk of short circuits, and improves the processability and welding of the battery.
Smart Images

Figure CN119170738A_ABST
Abstract
Description
[0001] The present invention is a divisional application of the invention patent application with application number 201980007285.2 (international application number: PCT / KR2019 / 001469, application date: February 1, 2019, invention name: electrode for lithium secondary battery, method for preparing the electrode and lithium secondary battery including the electrode). Technical Field
[0002] The present invention relates to an electrode for a lithium secondary battery, a method for preparing the electrode and a lithium secondary battery comprising the electrode. Background Art
[0003] As mobile devices are developed and demand grows, the demand for secondary batteries as power sources is rapidly increasing, and therefore, many studies have been conducted on batteries that can meet various demands.
[0004] Generally, in terms of battery shape, there is a high demand for cylindrical batteries and pouch-shaped batteries that can be applied to products with smaller thickness (such as mobile phones), and in terms of materials, there is a high demand for lithium secondary batteries such as lithium cobalt polymer batteries with high energy density, high discharge voltage and high safety.
[0005] One of the main research projects on secondary batteries is to improve safety. The main cause of accidents related to battery safety is caused by the occurrence of abnormally high temperature conditions due to short circuits between the positive and negative electrodes. In other words, in order to maintain electrical insulation under normal circumstances, a separator is provided between the positive and negative electrodes. However, conventional separators alone have limitations in abnormal abuse situations such as overcharging or overdischarging of the battery, internal short circuits due to dendritic growth of electrode materials or impurities, piercing of the battery by sharp objects such as nails or screws, or excessive deformation of the battery due to external forces.
[0006] Generally, a microporous membrane composed of a polyolefin resin is mainly used as a separator, but the heat resistance temperature of the membrane is about 120°C to 160°C, which means that the heat resistance of the membrane is insufficient. Therefore, when an internal short circuit occurs, there is a problem that the short circuit portion expands due to the contraction of the separator caused by the short circuit reaction heat, resulting in thermal runaway that generates more and higher reaction heat.
[0007] In addition, generally, a cylindrical secondary battery is manufactured by cutting the positive electrode and the negative electrode into a constant size and overlapping the cut electrodes layer by layer. Here, because there is a very small needle-like sharp part at the edge of the positive electrode or the negative electrode coated with a polymer electrolyte, when the electrodes are stacked, this part will have a slight internal short circuit, which will have an adverse effect on the battery performance. In particular, since the edge is more irregular than the inside when the polymer electrolyte is coated, the possibility of causing a short circuit due to uneven coating is high. In addition, when the upper and lower electrode layers are completely overlapped when the electrodes are stacked, a short circuit may occur between the positive electrode and the negative electrode.
[0008] As described above, various methods for reducing the possibility of cell deformation, external impact, or physical short circuit between a positive electrode and a negative electrode have been studied.
[0009] For example, in order to prevent a short circuit in a complete battery due to the contact of the electrode joint with the upper part of the electrode assembly by the movement of the electrode assembly, a method of attaching an insulating tape of a predetermined size to the electrode joint adjacent to the upper part of the current collector is used. As the insulating tape, a polyimide film is generally used, and it is generally recommended that the winding of the insulating tape is performed from the upper part of the current collector to a length extending slightly downward. In addition, in order to prevent unfolding, the tape is generally wound about 2 to 3 times.
[0010] However, the winding of the insulating tape is very complicated, and when the insulating tape is wound from the upper part of the current collector to a length extending slightly downward, this part may cause the thickness of the electrode assembly to increase. In addition, there is a problem that the tape is easy to unfold when the electrode joint is bent.
[0011] Korean Unexamined Patent Application Publication No. 10-2015-0031724 discloses a secondary battery.
[0012] [Prior art literature]
[0013] [Patent Document]
[0014] Korean Unexamined Patent Application Publication No.10-2015-0031724 Summary of the invention
[0015] Technical issues
[0016] The present invention aims to provide an electrode for a lithium secondary battery, which has excellent insulation between electrodes in a battery assembly and excellent cohesive strength between an electrode active material layer and an insulating layer, thereby improving the quality and stability of the battery.
[0017] In addition, the present invention is directed to providing an electrode for a lithium secondary battery, which can significantly prevent corrosion from occurring at each of an electrode active material layer and an insulating layer in an overlapping region between the electrode active material layer and the insulating layer.
[0018] In addition, the present invention is intended to provide a method for preparing an electrode of a lithium secondary battery, which can improve the insulation between electrodes in a battery assembly and the cohesive strength between an electrode active material layer and an insulating layer.
[0019] In addition, the present invention is directed to providing a lithium secondary battery including an electrode for a lithium secondary battery.
[0020] Technical Solution
[0021] The present invention provides an electrode for a lithium secondary battery, the electrode for a lithium secondary battery comprising: an electrode current collector; an electrode active material layer, the electrode active material layer is formed on the electrode current collector; and an insulating layer, the insulating layer is formed on the electrode current collector and overlaps with the electrode active material layer in a partial area. Here, when the thickness of the electrode active material layer in the area where the electrode active material layer does not overlap with the insulating layer is d1, and the thickness of the insulating layer in the area where the electrode active material layer does not overlap with the insulating layer is d2, d2 / d1 is 0.02 to 0.4.
[0022] In addition, the present invention provides a method for preparing the above-mentioned electrode for a lithium secondary battery, the method comprising the following steps: forming an undried electrode active material layer by coating an active material slurry composite on an electrode current collector; forming an undried insulating layer by coating a composite for forming an insulating layer so as to overlap with the undried electrode active material layer in a partial area; and simultaneously drying the undried electrode active material layer and the undried insulating layer.
[0023] In addition, the present invention provides a lithium secondary battery, which includes the electrode for a lithium secondary battery.
[0024] Beneficial Effects
[0025] The electrode for a lithium secondary battery of the present invention includes an insulating layer having an area overlapping with an electrode active material layer, and by controlling the thickness ratio of the insulating layer, the insulation between the electrodes during battery assembly is excellent, and the cohesion between the electrode active material layer and the insulating layer is excellent, thereby improving the quality and stability of the battery.
[0026] In addition, the electrode for a lithium secondary battery can significantly prevent corrosion of the insulating layer or the electrode active material layer in the above-mentioned overlapping region.
[0027] In addition, according to the method for preparing an electrode for a lithium secondary battery of the present invention, for example, the coated undried electrode active material layer and the undried insulating layer are dried simultaneously, thereby improving the cohesive strength and processability between the electrode active material layer and the insulating layer. As a result, the quality and stability of the electrode for a lithium secondary battery and the lithium secondary battery including the electrode can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a scanning electron microscope (SEM) image showing a region where the insulating layer and the positive electrode active material layer overlap in the cross section of the positive electrode prepared in Example 1.
[0029] Figure 2 is a SEM image showing an overlapping region of the insulating layer and the positive electrode active material layer in the cross section of the positive electrode prepared in Example 2.
[0030] Figure 3 is a SEM image showing an overlapping region of the insulating layer and the positive electrode active material layer in the cross section of the positive electrode prepared in Comparative Example 1.
[0031] Figure 4 is a SEM image showing an overlapping region of the insulating layer and the positive electrode active material layer in the cross section of the positive electrode prepared in Comparative Example 2. DETAILED DESCRIPTION
[0032] Hereinafter, the present invention will be described in further detail to help understand the present invention. Herein, the terms and words used in the specification and claims should not be interpreted as limited to the general meaning or dictionary meaning, but should be interpreted according to the meaning and concept of the technical idea of the present invention based on the principle of the term concept appropriately defined by the inventor in order to explain the present invention in the best way.
[0033] The terms used in the specification are only used to explain specific examples, rather than to limit the present invention. Unless otherwise clearly indicated in the context, a singular expression includes a plural object.
[0034] The terms "comprising" and "having" used herein indicate the presence of features, quantities, stages, components or combinations thereof, and it should be understood that the possibility of the presence or addition of one or more other features, quantities, stages, components or combinations thereof is not precluded.
[0035] Unless expressly stated otherwise, "%" as used herein refers to weight percent (wt %).
[0036] In the specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% in the particle size distribution curve based on cumulative volume. The average particle size (D 50). Laser diffraction methods are generally capable of measuring particle sizes in the submicron to several millimeters range and can obtain results with high reproducibility and high resolution.
[0037] Hereinafter, the present invention will be described in detail.
[0038] Electrodes for lithium secondary batteries
[0039] The present invention provides an electrode for a lithium secondary battery, the electrode comprising: an electrode current collector; an electrode active material layer formed on the electrode current collector; and an insulating layer formed on the electrode current collector and overlapping with the electrode active material layer in a partial region. Here, when the thickness of the electrode active material layer in the region where the electrode active material layer does not overlap with the insulating layer is d1, and the thickness of the insulating layer in the region where the electrode active material layer does not overlap with the insulating layer is d2, d2 / d1 is 0.02 to 0.4.
[0040] The electrode for a lithium secondary battery includes an insulating layer having an overlapping area with an electrode active material layer, and by controlling the thickness of the insulating layer at a specific ratio, the electrode can have an improved cohesive strength between the insulating layer and the electrode active material layer, and sufficient insulation. In addition, since the electrode active material layer and the insulating layer overlap, the exposure of the electrode current collector can be minimized, thereby preventing a short circuit when a problem occurs in the shrinkage of the separator (such as contact between the positive electrode and the negative electrode), and improving the quality and stability of the battery.
[0041] An electrode for a lithium secondary battery includes an electrode current collector, an electrode active material layer, and an insulating layer.
[0042] The electrode current collector is not particularly limited, as long as it has high conductivity without causing chemical changes in the battery, and can be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or stainless steel or aluminum-cadmium alloy treated with carbon, nickel, titanium or silver on the surface. In addition, the electrode current collector can generally have a thickness of 3 μm to 500 μm, and fine concave-convex shapes can be formed on the surface of the current collector to improve the bonding strength with the electrode active material. For example, the electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0043] The electrode active material layer is formed on the electrode current collector.
[0044] The electrode active material layer may include an electrode active material.
[0045] The electrode active material may include a positive electrode active material or a negative electrode active material. Preferably, the electrode active material includes a positive electrode active material.
[0046] The positive electrode active material is not particularly limited and may be, for example, a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium-based nickel oxide such as LiMnO3, LiMn2O3 or LiMnO2; 1+c1 Mn 2-c1 Lithium manganese oxide represented by O4 (0≤c1≤0.33); lithium copper oxide (Li2CuO2); vanadium oxide such as LiV3O8, V2O5 or Cu2V2O7; 1-c2 Ni-site lithium nickel oxide represented by Mc2O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and 0.01≤c2≤0.3); LiMn 2-c3 A lithium manganese composite oxide represented by Mc3O2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and 0.01≤c3≤0.1) or Li2Mn3MO8 (wherein M is at least one selected from Fe, Co, Ni, Cu and Zn); or LiMn2O4 in which a portion of Li in the formula is replaced by an alkaline earth metal ion, but the present invention is not limited thereto. The positive electrode may be lithium metal.
[0047] The negative electrode active material is not particularly limited and may be, for example, a compound capable of reversibly intercalating and deintercalating lithium. Specific examples of the negative electrode active material may be a carbon-based material such as artificial graphite, natural graphite, graphitized carbon fiber, or amorphous carbon; a metal compound capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; a metal compound capable of alloying with lithium such as SiO β (0<β<2), metal oxides capable of being doped and undoped with lithium, such as SnO2, vanadium oxide or lithium vanadium oxide; or a composite containing a metal compound and a carbon-based material, such as a Si-C composite or a Sn-C composite, and any one of them or a mixture of two or more thereof may also be used. In addition, as a negative electrode active material, a metallic lithium film may be used. In addition, as a carbon material, both low-crystalline carbon and high-crystalline carbon may be used. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbon such as coke derived from petroleum or coal tar pitch.
[0048] The electrode active material layer may include 80 wt % to 99.5 wt %, for example 88 wt % to 99 wt %, of the electrode active material relative to the total weight of the electrode active material layer.
[0049] The electrode active material layer may further include a binder for the electrode active material layer.
[0050] The binder of the electrode active material layer may be used to improve the cohesive strength between the electrode active materials and the adhesive strength between the electrode active materials and the electrode current collector.
[0051] The binder for the electrode active material layer may be used to improve the attachment between the electrode active materials and the bonding strength between the electrode active materials and the electrode current collector.
[0052] Specifically, the binder for the electrode active material layer can be at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, styrene-butadiene rubber, polyethylene oxide, carboxymethyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyvinyl acetate copolymer, polyarylate and a low molecular weight compound having a molecular weight of 10,000 g / mol or less, and polyvinylidene fluoride is most preferred in terms of adhesiveness, chemical resistance and electrochemical stability.
[0053] The binder for the electrode active material layer may be included in an amount of 0.1 wt % to 10 wt %, for example 0.5 wt % to 5 wt %, relative to the total weight of the electrode active material layer.
[0054] In addition to the above-mentioned components, the electrode active material layer may also include a conductive material. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite can be used; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon powders, aluminum powders or nickel powders; conductive whiskers composed of zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives.
[0055] The conductive material may be included in an amount of 0.1 wt % to 20 wt %, preferably 0.3 wt % to 10 wt %, relative to the total weight of the electrode active material layer.
[0056] The insulating layer is formed on the electrode current collector to overlap with the electrode active material layer in a partial region. For example, the electrode active material layer and the insulating layer may be stacked or formed to overlap with each other in a partial region.
[0057] The insulating layer may be formed of a composite for forming an insulating layer of a lithium secondary battery, the composite including a binder for the insulating layer and a solvent.
[0058] The binder for the insulating layer is a component that imparts bonding ability to, for example, an electrode current collector and / or an electrode active material layer to the insulating layer.
[0059] Specifically, the binder for the insulating layer may be at least one binder polymer selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, styrene-butadiene rubber, polyethylene oxide, carboxymethyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyvinyl acetate copolymer, polyarylate, and a low molecular weight compound having a molecular weight of 10,000 g / mol or less. Among these binder polymers, the binder polymer is preferably polyvinylidene fluoride in terms of adhesion, chemical resistance, and electrochemical stability.
[0060] The weight average molecular weight of the polyvinylidene fluoride polymer may be 400,000 to 1,500,000, and preferably 600,000 to 1,200,000, in consideration of improving the adhesive strength to the above-mentioned electrode active material layer and obtaining a desired viscosity.
[0061] In terms of improving the solubility of the composite, the melting point of the polyvinylidene fluoride polymer may be 150°C to 180°C, preferably 165°C to 175°C.
[0062] The binder for the insulating layer may be the same material as the binder for the electrode active material layer described above. In this case, as described below, the cohesive strength in the overlapping region of the electrode active material layer and the insulating layer can be further improved, and the improvement of product safety and quality can be expected, and in terms of improving adhesive strength, cohesive strength and processability such as weldability, the binder for the electrode active material layer is preferred.
[0063] The solvent may be appropriately selected in consideration of the solubility and viscosity of a binder or a colorant for the insulating layer, and is, for example, methylpyrrolidone (NMP).
[0064] The insulating layer may further include at least one colorant selected from the group consisting of an organic dye, an oil-soluble dye, and an organic phosphor. The colorant may be included in the insulating layer to determine a formation or orientation position of the insulating layer using a detector.
[0065] Since colorants including organic dyes, oil-soluble dyes and / or organic phosphors have excellent solubility in solvents compared to pigments insoluble in organic solvents, when used, the dye or phosphor can be uniformly distributed in the insulating layer. Compared with using a pigment as a colorant, the coagulation of the colorant of the composite for forming the insulating layer can be significantly reduced, and when a dispersant is used to prevent the coagulation of the pigment, phase separation, reduction in liquid stability, and corrosion in the overlapping region of the electrode active material layer and the insulating layer can be significantly reduced.
[0066] The organic dye can be at least one selected from the group consisting of anthraquinone-based dyes, aniline-based azo dyes, triphenylmethane-based dyes, pyrazole-based dyes, pyridone-based dyes, picolinone-based dyes, oxyphenol-based dyes, benzylidene dyes and xanthene-based dyes, preferably, at least one selected from the group consisting of benzylidene dyes and azo dyes, more preferably benzylidene dyes, so as to improve the liquid stability and prevent phase separation.
[0067] As the organic phosphor, for example, an organic phosphor having a carboxyl group, a phosphoric acid group, or both may be used.
[0068] The oil-soluble dye may be a benzimidazolone-based compound, an azo compound, a quinoline compound, a quinacridone-based compound, a phthalocyanine-based compound, a diketopyrrolopyrrole (DPP)-based compound or a combination of two or more thereof, and preferably, may be a benzimidazolone-based compound, an azo compound or a combination of two or more thereof to improve recognition.
[0069] In addition to organic dyes, oil-soluble dyes and / or organic phosphors, the colorant may also include metal ions. Specifically, the colorant may include organic dyes, oil-soluble dyes and / or organic phosphors that form a complex salt structure with the metal ions. Since the organic dyes, oil-soluble dyes and / or organic phosphors form a complex salt structure with the metal ions, they have excellent solubility or dispersibility in organic solvents, excellent light resistance, stability and heat resistance, can further improve clarity, and can achieve uniform distribution in the composite.
[0070] The metal ion is not particularly limited as long as it can form a complex salt structure with the above-mentioned organic dye, oil-soluble dye and / or organic phosphor, and may include, for example, copper, cobalt, chromium, nickel and / or iron ions, and preferably includes chromium ions.
[0071] In a region where the electrode active material layer and the insulating layer overlap, the electrode active material layer may be formed obliquely.
[0072] The length of the region where the electrode active material layer and the insulating layer overlap may be 0.05 mm to 1.3 mm, and preferably 0.1 mm to 1.0 mm. In this case, in order to minimize the capacity reduction caused by the overlap of the electrode active material layer and the insulating layer, the above range is preferred, and the cohesive strength or adhesive strength between the electrode active material layer and the insulating layer is further improved.
[0073] In order to prevent the capacity from being reduced due to the overlap of the electrode active material layer and the insulating layer, the thickness of the insulating layer in the region overlapping with the electrode active material layer may be made smaller toward the electrode active material layer.
[0074] In the region where the electrode active material layer and the insulating layer overlap, when the thickness of the insulating layer at the end of the electrode active material layer is A0 and the thickness of the insulating layer at the end of the insulating layer is A, A / A0 may be 0.05 or more and less than 1, preferably 0.1 to 0.7, and more preferably 0.2 to 0.4. Within the above range, the capacity reduction caused by the overlap of the electrode active material layer and the insulating layer can be minimized, the cohesive strength or adhesive strength between the insulating layer and the electrode active material layer can be further improved, and the interface rupture caused by corrosion between the insulating layer and the active material layer can be prevented.
[0075] A0 may be 3 μm to 20 μm, preferably 5 μm to 12 μm, and A may be 0.15 μm or more and less than 20 μm, and preferably 1 μm to 5 μm.
[0076] With respect to the electrode active material layer or the insulating layer in the region where the electrode active material layer and the insulating layer do not overlap, for example, in the region other than the overlapping region, when the thickness of the electrode active material layer in the region where the electrode active material layer and the insulating layer do not overlap is d1, and the thickness of the insulating layer in the region where the electrode active material layer and the insulating layer do not overlap is d2, d2 / d1 can be 0.02 to 0.4, preferably 0.05 to 0.1.
[0077] The electrode for a lithium secondary battery can have excellent insulation and excellent bonding strength due to the above-mentioned range of the thickness ratio of the electrode active material layer and the insulating layer. By stacking a plurality of electrodes, there will be no welding interference of the insulating layer in the production of the lithium secondary battery, and the minimum thickness of the insulating layer is ensured to maintain insulation, thereby improving the quality and stability of the battery. When d2 / d1 is less than 0.02, sufficient insulation of the insulating layer may not be ensured, and there is concern about product defects or reduced battery capacity due to corrosion occurring in the electrode active material layer. When d2 / d1 is greater than 0.4, the thickness of the insulating layer may be excessively increased, and welding interference may be caused by the insulating layer when stacking a plurality of electrodes, resulting in a short circuit in the welded portion, so that a capacity reduction or an increase in resistance may occur.
[0078] In the region where the electrode active material layer and the insulating layer do not overlap, the thickness (d2) of the insulating layer may be 3 μm to 20 μm, and in the region where the electrode active material layer and the insulating layer do not overlap, the thickness (d1) of the electrode active material layer may be 50 μm to 150 μm. Within the above range, the above insulation, adhesion and processability may be more excellently achieved.
[0079] The electrode for a lithium secondary battery may be a positive electrode for a lithium secondary battery or a negative electrode for a lithium secondary battery, and is preferably a positive electrode for a lithium secondary battery.
[0080] The electrode for the lithium secondary battery may include an insulating layer formed to overlap with the electrode active material layer in a partial region, and when the thickness of the insulating layer is controlled at a specific ratio, the cohesive strength between the insulating layer and the electrode active material layer can be increased, and sufficient insulation can be exerted. In addition, the problem of capacity reduction or resistance increase due to battery short circuit that may occur when stacking multiple electrodes for lithium secondary batteries can be prevented, and the battery quality and stability can be improved.
[0081] Method for preparing electrode for lithium secondary battery
[0082] In addition, the present invention provides a method for preparing the electrode for a lithium secondary battery.
[0083] The method for preparing an electrode for a lithium secondary battery comprises the following steps: forming an undried electrode active material layer by coating an active material slurry composite on an electrode current collector; forming an undried insulating layer by coating a composite for forming an insulating layer so as to overlap with the undried electrode active material layer in a partial area; and simultaneously drying the undried electrode active material layer and the undried insulating layer.
[0084] Specifically, the preparation method of the electrode for the lithium secondary battery of the present invention can be a wet-wet coating method. For example, the wet coating method is to form an undried electrode active material layer by coating an active material slurry composite on an electrode current collector without drying the slurry composite, to form an undried insulating layer by coating a composite for forming an insulating layer to overlap partially with the undried electrode active material layer, and to simultaneously dry the undried electrode active material layer and the undried insulating layer to form an undried electrode active material layer. When the electrode active material layer and the insulating layer are formed using the above-mentioned wet coating method, the cohesive strength between the electrode active material layer and the insulating layer is increased compared to when the insulating layer is formed on the dried electrode active material layer. In addition, since the method only includes one drying process, the preparation process is simple, and the overlapping area is controlled to have a desired length under the processing conditions, thereby improving the cohesive strength, weldability and processability, and therefore, the defects in the lithium secondary battery produced by the method described can be prevented. As a result, the lithium secondary battery can have excellent quality and stability.
[0085] Hereinafter, a method of preparing an electrode for a lithium secondary battery will be described in detail.
[0086] First, an undried electrode active material layer is formed by coating an active material slurry composite on an electrode current collector.
[0087] The electrode current collector may be the same as the above-described electrode current collector in terms of type, material, and thickness.
[0088] The active material slurry composite may be applied to the electrode current collector to form an undried electrode active material layer. The active material slurry composite may be a positive electrode active material slurry composite or a negative electrode active material slurry composite, and the positive electrode active material slurry composite may contain a positive electrode active material, a binder and / or a conductive material for an electrode active material layer, and the negative electrode active material slurry composite may contain a negative electrode active material, a binder and / or a conductive material for an electrode active material layer. The positive electrode active material, the negative electrode active material, the binder and / or the conductive material may be the above-mentioned positive electrode active material, the negative electrode active material, the binder and / or the conductive material for an electrode active material layer.
[0089] The active material slurry compound may further include a solvent in addition to the above-mentioned components, and the solvent may be, for example, NMP in consideration of the solubility and viscosity of the active material slurry compound.
[0090] The active material slurry composite may have a viscosity of 5,000 to 15,000 cP at 25° C., preferably 6,000 to 13,000 cP, and within this range, the undried electrode active material layer or the cohesive strength of the electrode active material layer may be improved, and coating property and processability may be further improved.
[0091] The active material slurry composite can be coated on the electrode current collector to form an undried electrode active material layer. "Undried" as used herein includes the case where the active material slurry composite is coated without drying, and the case where the active material slurry composite is not substantially dried and a drying process is not performed.
[0092] Subsequently, an undried insulating layer is formed by coating the composite for forming an insulating layer of a lithium secondary battery so as to overlap with the undried electrode active material layer in a partial region.
[0093] Meanwhile, the composite for forming the insulating layer may include the above-mentioned binder and solvent for the insulating layer, and, if necessary, further include the above-mentioned colorant.
[0094] The binder for the insulating layer may be included in an amount of 5 to 15 parts by weight, preferably 8 to 12 parts by weight, relative to 100 parts by weight of the solvent, in order to achieve desired viscosity and ease of coating.
[0095] A colorant may be included in the composite so that a position where the insulating layer is formed is determined using a detector while coating the insulating layer using the composite for forming the insulating layer.
[0096] The colorant may include the above-mentioned organic dyes, oil-soluble dyes and / or organic phosphors.
[0097] Conventional composites for forming insulating layers generally use pigments such as organic pigments or inorganic pigments. However, in general, pigments such as inorganic pigments or organic pigments are insoluble in water or organic solvents, and are easily coagulated in the composite, and therefore it is difficult to evenly distribute the pigment in the insulating layer. In order to prevent the problem of such pigment coagulation, a dispersant can be added to the composite for forming the insulating layer. However, in order to perform the process of overlapping the electrode active material layer and the insulating layer, the composite for forming the insulating layer requires a certain level or higher viscosity, and, despite the addition of a dispersant, the composite whose viscosity meets the above requirements may also have the problem of difficulty in dispersing the pigment and easy coagulation.
[0098] However, when a colorant including an organic dye, an oil-soluble dye and / or an organic phosphor is used, the colorant has excellent solubility in a solvent and improved liquid stability even in a composite for forming an insulating layer having a high viscosity requirement, thereby showing excellent coating properties of the composite for forming an insulating layer and preventing corrosion of the electrode active material layer when forming the insulating layer.
[0099] Relative to 100 parts by weight of the solvent, 0.01 parts by weight to 10 parts by weight of the colorant may be included, preferably 0.01 parts by weight to 1 part by weight of the colorant, and more preferably 0.05 parts by weight to 0.5 parts by weight of the colorant, and when the colorant is used within the above range, it is preferred that visibility is ensured when a detector is used to determine the insulating layer formation position and that the colorant is uniformly distributed in the insulating layer.
[0100] The solubility of the colorant in the solvent may be 300 to 500 g / L, and preferably 350 to 450 g / L at 25° C., and the above range is preferred in terms of uniform distribution of the colorant and improved solubility.
[0101] The solvent may be appropriately selected in consideration of the solubility and viscosity of a binder or a colorant for the insulating layer, and may be NMP, for example.
[0102] The solid content of the composite for forming an insulating layer of a lithium secondary battery may be 5 wt % to 15 wt %, and preferably 8 wt % to 12 wt %. The above range is preferred in terms of ensuring desired coating properties and viscosity range.
[0103] The viscosity of the compound for forming the insulating layer at 25° C. may be 1,000 to 10,000 cP, preferably 5,000 to 8,000 cP. Within the above range, the viscosity difference with the electrode active material layer can be minimized, and corrosion of the electrode active material layer caused by the low viscosity of the compound for forming the insulating layer can be effectively prevented.
[0104] The viscosity difference between the active material slurry compound and the compound for forming the insulating layer at 25° C. may be 5,000 cP or less, preferably 2,000 cP or less, and more preferably 1,000 cP or less. When the viscosity difference is within the above range, the adhesive strength or cohesive strength between the undried electrode active material layer and the undried insulating layer after drying can be further improved, and corrosion of the overlapping area can be effectively prevented.
[0105] When the undried electrode active material layer and the undried insulating layer are formed by the above method, the undried electrode active material layer and the undried insulating layer are dried simultaneously.
[0106] In the preparation method of the electrode for the lithium secondary battery according to the present invention, instead of forming the electrode active material layer by coating and drying the active material slurry composite and then coating the composite for forming the insulating layer, the undried electrode active material layer and the undried insulating layer can be dried simultaneously, thereby further improving the cohesive strength or adhesive strength between the electrode active material layer and the insulating layer. In addition, for this reason, the overlapping area of the undried electrode active material layer and the undried insulating layer or the overlapping area of the electrode active material layer and the insulating layer becomes relatively long, and the insulating layer can be formed to have a very small thickness in the overlapping area, thereby significantly improving the processability, weldability, quality and stability of the battery.
[0107] The drying process is not particularly limited as long as the undried electrode active material layer and the undried insulating layer can be fully dried, and a conventional drying method known in the art can be used. For example, a drying method selected from a convection method, a direct heating method, and an induction heating method can be applied, and specifically, performed at 50° C. to 180° C. for 1 minute to 5 minutes.
[0108] Secondary battery
[0109] In addition, the present invention provides a lithium secondary battery including the electrode for a lithium secondary battery.
[0110] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode arranged opposite to the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. Here, as the positive electrode and / or the negative electrode, the above-mentioned electrode for the lithium secondary battery can be used. In addition, the lithium secondary battery can selectively include: a battery housing containing an electrode assembly including a positive electrode, a negative electrode and a separator; and a sealing member for sealing the battery housing.
[0111] Meanwhile, in lithium secondary batteries, the separator is not particularly limited, as long as it is commonly used in lithium secondary batteries to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions, and in particular, the separator has low resistance to the ion mobility of the electrolyte and has excellent electrolyte impregnation ability. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared from a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a stacked structure including two or more layers can be used. In addition, conventional porous non-woven fabrics can be used, for example, non-woven fabrics formed of high melting point glass fibers or polyethylene terephthalate fibers. In addition, a coated copolymer including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer structure or a multilayer structure.
[0112] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in the production of a lithium secondary battery, but the present invention is not limited thereto.
[0113] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0114] There is no particular limitation on the organic solvent as long as it can be used as a medium that enables the migration of ions participating in the electrochemical reaction of the battery. Specifically, the organic solvent may be an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone; an ether-based solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene or fluorobenzene; a carbonate-based solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); an alcohol-based solvent such as ethanol or isopropanol; a nitrile-based solvent such as R-CN (R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may contain a double-bonded aromatic ring or an ether bond); an amide-based solvent such as dimethylformamide; a dioxolane-based solvent such as 1,3-dioxolane; or a sulfolane-based solvent. Among them, carbonate solvents are preferably used, and more preferably a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) and low-viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) having high ionic conductivity and high dielectric constant to improve the charge and discharge performance of the battery is used. In this case, by using a mixture of cyclic carbonates and chain carbonates in a volume ratio of about 1:1 to about 1:9, the electrolyte solution can exhibit excellent performance.
[0115] The lithium salt is not particularly limited as long as it is a compound that can provide lithium ions for lithium secondary batteries. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2. The concentration of the lithium salt is preferably in the range of 0.1M to 2.0M. When the concentration of the lithium salt is included in the above range, the electrolyte has suitable conductivity and viscosity, and thus can exhibit excellent electrolytic performance. Therefore, lithium ions can be effectively migrated.
[0116] In order to improve the life characteristics of the battery, suppress the decline of the battery capacity and increase the discharge capacity of the battery, in addition to the components of the electrolyte, the electrolyte may also include one or more types of additives, for example, such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride halogenated alkylene carbonate compounds. Here, relative to the total weight of the electrolyte, 0.1wt% to 5wt% additives may be included.
[0117] The lithium secondary battery according to the example may be used in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).
[0118] Therefore, according to another exemplary embodiment of the present invention, there is provided a battery module including a lithium secondary battery as a unit battery and a battery pack including the battery module.
[0119] The battery module or battery pack may be used as a power source for any one or more of large and medium-sized devices including power tools, electric vehicles such as electric vehicles (EVs), hybrid vehicles, and plug-in hybrid vehicles (PHEVs), and power storage systems.
[0120] The shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a columnar shape, a pouch shape, or a coin shape.
[0121] The lithium secondary battery according to the present invention can be used not only in a battery cell used as a power source for small devices but also can be preferably used as a unit battery in a medium or large battery module including a plurality of battery cells.
[0122] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments described herein.
[0123] Examples and Comparative Examples
[0124] Example 1: Preparation of positive electrode for lithium secondary battery
[0125] By mixing LiNi as the positive electrode active material at a weight ratio of 97.3:1.5:1.2 0.6 Mn 0.2 Co 0.2O2, carbon black as a conductive material, PVdF (trade name: KF9700, manufacturer: Kureha, weight average molecular weight: 880,000) as a binder for the electrode active material layer, and the mixture was added to an NMP solvent so that the solid content was 69 wt% to prepare a positive electrode active material slurry composite with a viscosity of 8,000 cP at 25°C.
[0126] The composite for forming the insulating layer was prepared by dissolving 9 parts by weight of PVdF (trade name: KF9700, manufacturer: Kureha, weight average molecular weight: 880,000) as a binder for the insulating layer and 0.1 parts by weight of benzylidene dye Yellow 081 (manufactured by BASF) as an organic dye in 100 parts by weight of NMP. Here, the viscosity of the composite for forming the insulating layer was 6,000 cP.
[0127] Thereafter, a undried positive electrode active material layer having a thickness of 165 μm was formed by coating the positive electrode active material slurry composite on an aluminum current collector, and a undried insulating layer having a thickness of 15 μm was formed by coating a composite for forming an insulating layer on the aluminum current collector to overlap with the undried positive electrode active material layer in a partial region.
[0128] Afterwards, a positive electrode for a lithium secondary battery (size: 132 mm×104 mm) was prepared by simultaneously drying the undried positive electrode active material layer and the undried insulating layer at 160° C. for about 3 minutes, and rolling the formed positive electrode active material layer and the insulating layer.
[0129] In the positive electrode for a lithium secondary battery of Example 1, in the area where the positive electrode active material layer does not overlap with the insulating layer, the thickness of the positive electrode active material layer is 80 μm, the thickness of the insulating layer is 7 μm, the length of the overlapping area is 0.5 mm, A is 2.1 μm, and A0 is 7 μm.
[0130] In Example 1, the ratio (d2 / d1) of the thickness of the insulating layer in the area where the electrode active material layer and the insulating layer do not overlap to the thickness of the electrode active material layer in the area where the electrode active material layer and the insulating layer do not overlap is approximately 0.088, and A / A0 in the area where the electrode active material layer and the insulating layer overlap is 0.3.
[0131] Example 2: Preparation of positive electrode for lithium secondary battery
[0132] A positive electrode for a lithium secondary battery (size: 132 mm×104 mm) was prepared in the same manner as described in Example 1, except that the composite for forming an insulating layer was applied at a flow rate about 50% lower than that of Example 1.
[0133] In the positive electrode for a lithium secondary battery prepared in Example 2, in the area where the positive electrode active material layer does not overlap with the insulating layer, the thickness of the positive electrode active material layer is 80 μm, the thickness of the insulating layer is 3 μm, the length of the overlapping area is 0.5 mm, A is 0.5 μm, and A0 is 3 μm.
[0134] In Example 2, the ratio (d2 / d1) of the thickness of the insulating layer in the region where the electrode active material layer does not overlap with the insulating layer to the thickness of the electrode active material layer in the region where the electrode active material layer does not overlap with the insulating layer is approximately 0.038, and A / A0 in the region where the electrode active material layer overlaps with the insulating layer is approximately 0.17.
[0135] Comparative Example 1: Preparation of a positive electrode for a lithium secondary battery
[0136] By mixing LiNi as the positive electrode active material at a weight ratio of 97.3:1.5:1.2 0.6 Mn 0.2 Co 0.2 O2, carbon black as a conductive material, PVdF (trade name: KF9700, manufacturer: Kureha, weight average molecular weight: 880,000) as a binder for the electrode active material layer, and the mixture was added to an NMP solvent so that the solid content was 69 wt % to prepare a positive electrode active material slurry composite with a viscosity of 8,000 cP at 25°C.
[0137] The composite for forming the insulating layer was prepared by dissolving 12 parts by weight of PVdF (trade name: KF9700, manufacturer: Kureha, weight average molecular weight: 280,000) as a binder for the insulating layer and 0.1 parts by weight of benzylidene dye Yellow 81 (manufactured by BASF) as an organic dye in 100 parts by weight of NMP. Here, the viscosity of the composite for forming the insulating layer was 670 cP.
[0138] A positive electrode for a lithium secondary battery (size: 132 mm×104 mm) was prepared in the same manner as described in Example 1 except that the positive active material slurry composite prepared above and the composite for forming the insulating layer were used.
[0139] In the positive electrode for a lithium secondary battery of Comparative Example 1, in the region where the positive electrode active material layer does not overlap with the insulating layer, the thickness of the positive electrode active material layer is 80 μm, the thickness of the insulating layer is 1 μm, and the length of the overlapping region is 0.5 mm. However, corrosion occurs in the region where the positive electrode active material layer overlaps with the insulating layer, and A and A0 cannot be determined.
[0140] In Comparative Example 1, the ratio (d2 / d1) of the thickness of the insulating layer in the region where the electrode active material layer and the insulating layer do not overlap to the thickness of the electrode active material layer in the region where the electrode active material layer does not overlap with the insulating layer is approximately 0.013.
[0141] Comparative Example 2: Preparation of a positive electrode for a lithium secondary battery
[0142] The positive active material slurry composite prepared in Example 1 was coated on an aluminum current collector and dried at 160° C. for 3 minutes to form a dried positive active material layer.
[0143] A positive electrode for a lithium secondary battery of Comparative Example 2 (size: 132 mm×104 mm) was prepared by coating the composite for forming an insulating layer prepared in Example 1 on an aluminum current collector to form a dried insulating layer so as to overlap with the dried positive electrode active material layer in a partial area, and drying the composite at 160° C. for 3 minutes.
[0144] In the area where the positive electrode active material layer does not overlap with the insulating layer, the thickness of the positive electrode active material layer is 80 μm, the thickness of the insulating layer is 35.2 μm, the length of the overlapping area is 0.5 mm, A is 9.2 μm, and A0 is 53 μm.
[0145] In Comparative Example 2, the ratio (d2 / d1) of the thickness of the insulating layer in the region where the electrode active material layer and the insulating layer do not overlap to the thickness of the electrode active material layer in the region where the electrode active material layer does not overlap with the insulating layer is 0.44, and in the region where the electrode active material layer and the insulating layer overlap, A / A0 is approximately 0.17.
[0146] Experimental Example 1: Evaluation by Scanning Electron Microscope (SEM)
[0147] The cross sections of the overlapping regions in the cross sections of the positive electrodes prepared by Example 1 and Example 2 and Comparative Example 1 and Comparative Example 2 were observed using a scanning electron microscope. The results were as follows: Figures 1 to 4 Shown in.
[0148] Reference Figure 1 and Figure 2 , it can be confirmed that, in the positive electrodes of Examples 1 and 2, the overlapping regions of the insulating layer and the electrode active material layer are formed with excellent cohesive strength and no corrosion occurs.
[0149] However, referring to Figure 3 , it can be confirmed that the positive electrode of Comparative Example 1 is not suitable for products because insulation cannot be sufficiently achieved due to corrosion in the overlapping area of the insulating layer and the electrode active material layer, resulting in defective products.
[0150] In addition, refer to Figure 4 , the positive electrode of Comparative Example 2 is not corroded, but the insulating layer formed by the dry coating method is thicker than the electrode active material layer, as described below, which may cause the capacity to decrease as the thickness of the insulating layer increases. In addition, the positive electrode of Comparative Example 2 is formed in such a way that the height of the end of the insulating layer is higher than the thickness of the electrode active material layer. However, when the above positive electrode is applied to the roll-to-roll process, the risk of the electrode roll being defective is high due to lifting at the end of the electrode, which is undesirable because it increases the possibility of defective products.
[0151] Experimental Example 2: Evaluation of Capacity Characteristics
[0152] <Production of Secondary Batteries>
[0153] The graphite (average particle size (D 50 ): 13 μm), acetylene black as a conductive material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener to prepare a negative electrode active material slurry composite. The negative electrode was prepared by coating the negative electrode active material slurry composite on one surface of a copper current collector layer (thickness: 6 μm), drying the coated composite at 150° C. and rolling. The thickness of the negative electrode was 95.9 μm.
[0154] The lithium secondary battery was produced by inserting a polypropylene separator (thickness: 15 μm) between each positive electrode and negative electrode for the lithium secondary battery prepared in Examples 1 and 2 and Comparative Examples 1 and 2 and placing it in a shell, and then injecting an electrolyte into the shell to prepare an electrode assembly. The electrolyte used here was prepared by dissolving LiPF6 in a solvent prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 so that the final concentration of LiPF6 was 1M.
[0155] <Evaluation of Capacitance Characteristics>
[0156] The lithium secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2 were initially charged (0.3CCC / CV charging, 4.2V / 0.05C cut-off) and initially discharged (0.3CCC discharge, 2.5V cut-off), and the discharge capacity was evaluated. The results are shown in Table 1 below.
[0157] [Table 1]
[0158] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Discharge capacity(Ah) 60.3 60.1 59.5 58.2
[0159] Referring to Table 1, it can be confirmed that the electrodes for lithium secondary batteries and the lithium secondary batteries prepared in Examples 1 and 2 exhibited high discharge capacity since the insulating layer was formed with an appropriate thickness compared with the electrode active material layer.
[0160] However, when the electrode for lithium secondary battery prepared in Comparative Example 1 was used, the battery capacity decreased due to corrosion of the electrode active material layer. In addition, when the electrode for lithium secondary battery prepared in Comparative Example 2 was used, it was confirmed that the capacity of the electrode active material was insufficient and the battery capacity decreased because the insulating layer was too thick.
[0161] CROSS-REFERENCE TO RELATED APPLICATIONS
[0162] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0013008, filed on Feb. 1, 2018, which is hereby incorporated by reference in its entirety.
Claims
1. An electrode for a lithium secondary battery, the electrode comprising: Electrode current collector; an electrode active material layer formed on the electrode current collector; as well as an insulating layer formed on the electrode current collector and overlapping with the electrode active material layer in a partial region, Wherein, when the thickness of the electrode active material layer in the region where the electrode active material layer and the insulating layer do not overlap is d1, and the thickness of the insulating layer in the region where the electrode active material layer and the insulating layer do not overlap is d2, d2 / d1 is 0.02 to 0.4, and Wherein, in the region where the electrode active material layer overlaps the insulating layer, when the thickness of the insulating layer at the end of the electrode active material layer is A0, and the thickness of the insulating layer at the end of the insulating layer is A, A / A0 is greater than 0.05 and less than 1.
2. The electrode according to claim 1, wherein The length of the region where the electrode active material layer overlaps the insulating layer is 0.05 mm to 1.3 mm.
3. The electrode according to claim 1, wherein The length of the region where the electrode active material layer overlaps the insulating layer is 0.1 mm to 1 mm.
4. The electrode according to claim 1, wherein In a region where the electrode active material layer overlaps the insulating layer, the thickness of the insulating layer decreases toward the electrode active material layer.
5. The electrode according to claim 1, wherein A0 is 3 μm to 20 μm.
6. The electrode according to claim 5, wherein A is 0.15 μm or more and less than 20 μm.
7. The electrode according to claim 1, wherein In a region where the electrode active material layer does not overlap with the insulating layer, a thickness d2 of the insulating layer is 3 μm to 20 μm.
8. The electrode according to claim 1, wherein In a region where the electrode active material layer does not overlap the insulating layer, a thickness d1 of the electrode active material layer is 50 μm to 150 μm.
9. The electrode according to claim 1, wherein The electrode active material layer is formed obliquely in a region where the electrode active material layer overlaps the insulating layer.
10. A method for preparing an electrode for a lithium secondary battery according to any one of claims 1 to 9, the method comprising the following steps: forming an undried electrode active material layer by coating the active material slurry composite on the electrode current collector; forming an undried insulating layer by applying the composite for forming an insulating layer so as to overlap with the undried electrode active material layer in a partial region; as well as The undried electrode active material layer and the undried insulating layer are dried simultaneously.
11. The method according to claim 10, wherein: The difference in viscosity between the active material paste compound and the compound for forming the insulating layer at 25° C. is 5,000 cP or less.
12. The method according to claim 11, wherein: The compound for forming the insulating layer has a viscosity of 1,000 cP to 10,000 cP at 25° C.
13. The method according to claim 11, wherein: The active material slurry compound has a viscosity of 5,000 cP to 15,000 cP at 25°C.
14. The method according to claim 10, wherein: The compound for forming the insulating layer includes a binder and a solvent, and The composite for forming the insulating layer has a solid content of 5 wt % to 15 wt %. 15 . A lithium secondary battery, comprising the electrode for a lithium secondary battery according to claim 1 .
Citation Information
Patent Citations
Secondary battery
KR1020150031724A
Image Forming Apparatus that editable print page automatically
KR1020180013008A
